POLYMER PRODUCTS AND CHEMICAL PROCESSES : Techniques, Analysis, And Applications - Pethrick, R. A. (Richard Arthur), 1942-, author, editor of compilation 362671; Pearce, Eli M., author, editor of compilation 238536; Zaikov, G. E. (Gennadii Efremovich), 1935-, author, editor of compilation 517658 (Toronto : Apple Academic Press, 2021)
This new volume presents leading-edge research in the rapidly changing and evolving field of polymer science as well as on chemical processing. The topics in the book reflect the diversity of research advances in the production and application of modern polymeric materials and related areas, focusing on the preparation, characterization, and applications of polymers. Also covered are various manufacturing techniques. The book will help to fill the gap between theory and practice in industry.